Improving students’ critical thinking through Project-Based Learning (PBL) - Widyaningrum, Agnes; Hartarini, Yovita Mumpuni (EduLite: Journal of English Education, Literature and Culture, 2024)
The fourth industrial revolution impacts the education system and student learning. Education must be capable of developing and designing 21st-century life skills learning, one of which is critical thinking abilities. The PBL model is used to guide efforts. This research aims to improve student’s critical thinking through Project-Based Learning (PBL). This research used a quantitative method, which is a quasi-experimental research design, by applying a non-equivalent pre-test post-test control group design. The study was carried out at Semarang City High School. This study’s sample size was 200 students from Semarang City High School. The data were obtained through the critical thinking test. This research used a t-test with a significant level of 0.05 to analyze the data. Based on the research analysis, Students in the control group boosted their critical thinking score by 9.58 points, from 65 to 74.58. Meanwhile, the experimental group students’ critical thinking score jumped by 19.99 points, from 60.77 to 80.76. The increase in the critical thinking score is 10.41. The result also showed a Sig. (2-tailed) value of 0.000. This number is less than 0.05. It indicated that is accepted. Based on the result of the Sig. (2-tailed) value t-test calculation, it can be concluded that due to the diverse learning methods applied, there are disparities in students’ critical thinking results with the acceptance. Project-based learning improves students’ critical thinking skills. The conclusion is that the PBL paradigm improves students’ critical thinking skills.